FPGA-based Architecture of Direct Torque Control - Azaza Maher; Echaieb Kamel; Mami Abdelkader (International Journal of Reconfigurable and Embedded Systems (IJRES), 2017)
This paper presents an optimized FPGA architecture of a DTC “direct torque control” drive of an induction motor. The proposed architecture is based on variable fixed point world size and the use ipcores in order to achieve higher sampling frequency which leads to reduce the electromagnetic torque and flux ripples. The hardware implementation was experimentally validated, the results shows the effectiveness of the hardware DTC drive implementation by the minimization of the torque and flux ripple